YIELD AND CHEMICAL COMPOSITION OF WILD SUNFLOWER (TITHONIA DIVERSIFOLIA HEMSL A. GRAY) AND THE FEEDING VALUE OF WILD SUNFLOWER FORAGE MEAL IN BROILER CHICKEN DIETS - FARINU, G.O.; Odunsi, A.A.; AKINOLA, J.O.; TOGUN, V.A. (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to determine the forage yield and chemical composition of the green leaf, senescence leaf and inflorescence fractions of the wild sunflower and the value of wild sunflower forage meal (WSFM) as a feed resource in broiler chicken diets. Results showed that crude protein and ether extract contents were higher in green leaf compared to senescence leaf or inflorescence while soluble sugars, ADF and NDF were lower in the green leaf compared to either senescence leaf or inflorescence. Inclusion of WSFM in broiler starter diets indicated that feed intake, weight gain and feed conversion ratio were similar up to 5 % while they were significantly depressed at 7.5 O/u and 10.0 % levels. Crude protein retention was adversely affected by the 10 % WSFM diet. The cost of feed consumed per kg weight gain was in favour of WSFM inclusions up to 10 %.